2011
DOI: 10.1007/s10404-011-0788-3
|View full text |Cite
|
Sign up to set email alerts
|

A disposable, integrated loop-mediated isothermal amplification cassette with thermally actuated valves

Abstract: An inexpensive, disposable, integrated, polymer-based cassette for loop-mediated isothermal amplification (LAMP) of target nucleic acids was designed, fabricated, and tested. The LAMP chamber was equipped with single-use, thermally actuated valves made with a composite consisting of a mixture of PDMS and expandable microspheres. The effect of the composite composition on its expansion was investigated, and the valve's performance was evaluated. In its closed state, the valve can hold pressures as high as 200 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 50 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…Also, two-step reverses transcription (RT)-LAMP assays were developed for identifying RNA of the pathogen as the viability marker [9]. Recently, microfluidic LAMP assay was introduced as a rapid and portable identification test [10]; however, the microfluidic LAMP would be useful in the point-of-care for diagnostic purposes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, two-step reverses transcription (RT)-LAMP assays were developed for identifying RNA of the pathogen as the viability marker [9]. Recently, microfluidic LAMP assay was introduced as a rapid and portable identification test [10]; however, the microfluidic LAMP would be useful in the point-of-care for diagnostic purposes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acid-based molecular diagnostics have been simplified with the advent of isothermal amplification methods such as loop-mediated isothermal amplification (LAMP), reverse transcription loop-mediated isothermal amplification (RT-LAMP) [62,63], nucleic acid sequence based amplification (NASBA) [64,65], recombinase polymerase amplification (RPA) [66,67], and helicase dependent amplification (HDA) [68]. Isothermal amplification assays are very suitable for chip-based POC diagnostic applications due to their simple operation, high amplification efficiency, and easy detection.…”
Section: Isothermal Nucleic Acids Amplification Methodsmentioning
confidence: 99%
“…The sensitivity referred to less than 24 CFU/mL for bacteria and 8.6 fg/µL for DNA [57]. Chuang et al demonstrated a simple, low-cost surface plasmon resonance sensing cartridge based on the LAMP method for the one-site detection of hepatitis B virus [58][59][60][61][62][63][64][65][66]. The HBV template could be detected by an SPR-LAMP system in 17 minutes even at the detection limit of 2 fg/mL.…”
Section: Strategies To Miniaturize Isothermal Amplification Reactionsmentioning
confidence: 99%